Structure Data for "Insights into molecular cluster materials with adamantane-like core structures by considering dimer interactions" - Schwan, Sebastian; Mollenhauer, Doreen; Justus Liebig University Giessen (My University, 2022)
Calculated structural data of monomers, dimers, trimers and tetramers of cluster materials for the publication: Sebastian Schwan, Andreas J. Achazi, Ferdinand Ziese, Peter R. Schreiner, Kerstin volz, Stefanie Dehnen, Simone Sanna, Doreen Mollenhauer, "Insights into molecular cluster materials with adamantane-like core structures by considering dimer interactions". The structures were pre-optimized using CREST and GFN2-xTB, followed by an optimization at the B3LYP-D3(BJ)/cc-pVDZ level of theory. The file format is xyz.